Considerations as to an extended scheme of land purchase - Cherry, Richard R. (Statistical and Social Inquiry Society of Ireland, 1887)
There appears to be a general concensus of opinion that the Irish land question can only be finally settled by an extension, on a wide scale, of the system of land purchase inaugurated by Lord Ashbourne's Act, and by the creation of a large number of occupying owners throughout the country. I do not propose now to discuss the wisdom of this policy, but rather to consider how the objects sought for can best be attained, and in what manner a sound system of land tenure can thus be established, without any loss to the present landlords or to the state.
Read, Tuesday, 7th December, 1886
Keywords: Land purchase scheme; Irish land question; Land Purchase Act; Proposed land reform; 314.15